Elevated Fibroblast Growth Factor-23 as an Independent Predictor of All-Cause Mortality, Cardiovascular Events, and Progression to ESRD in Pre-Dialysis CKD: A Systematic Review and Meta-Analysis - Sri Puji Rahayuningsih; Drajad Priyono; Harnavi Harun; Deka Viotra (HM Publisher, 2025)
Background: Fibroblast growth factor-23 (FGF23) is a central hormone in mineral metabolism, with levels rising early in chronic kidney disease (CKD). While its role in the pathophysiology of CKD–Mineral and Bone Disorder (CKD-MBD) is established, its independent prognostic value for adverse outcomes in the pre-dialysis population remains a subject of intense investigation. We aimed to systematically quantify the association between elevated FGF23 levels and the risks of all-cause mortality, cardiovascular (CV) events, and progression to End-Stage Renal Disease (ESRD) in patients with pre-dialysis CKD. Methods: We conducted a systematic review and meta-analysis following PRISMA guidelines. A comprehensive search of PubMed, EMBASE, and the Cochrane Library was performed for prospective cohort studies published between January 2014 and December 2024 that evaluated the prognostic value of FGF23 in adult, pre-dialysis CKD patients. The primary outcomes were all-cause mortality, a composite of major cardiovascular events, and progression to ESRD. Hazard Ratios (HRs) were pooled using a random-effects model. Heterogeneity was assessed using the I² statistic, and publication bias was evaluated with funnel plots and Egger's test. Results: Seven prospective cohort studies involving 14,882 patients were included. The analysis revealed that elevated FGF23 was a significant independent predictor for all three outcomes. The pooled HR for all-cause mortality was 1.42 (95% CI: 1.28–1.58; I²=72%), for cardiovascular events was 1.39 (95% CI: 1.21–1.59; I²=78%), and for progression to ESRD was 1.55 (95% CI: 1.35–1.78; I²=65%). The associations remained significant after adjustment for traditional CKD-MBD markers and renal function in the primary studies. Sensitivity analyses confirmed the robustness of these findings. Conclusion: This meta-analysis provides strong evidence that elevated FGF23 is a potent and independent predictor of all-cause mortality, cardiovascular events, and progression to ESRD in the pre-dialysis CKD population. These findings underscore the potential utility of FGF23 as a key biomarker for risk stratification and suggest it may be a critical therapeutic target to improve outcomes in this vulnerable population.